PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII SMPN 26 PADANG - Ayunda Zahra (Jurnal Edukasi dan Penelitian Matematika, 2023)
Mathematical communication skills are crucial to learning. The class VIII evaluation of SMPN 26 Padang demonstrates that pupils' mathematics communication skills require improvement. Problem-Based Learning (PBL) helps solve this issue. This study examined the mathematics communication skills of grade VIII students at SMPN 26 Padang who were taught using Problem Based Learning (PBL) and compared them to those taught using conventional techniques. This study also tracked students' mathematics communication skills during PBL implementation. Non-equivalent Posttest Control Group Design was utilized in this quasi-experimental study.PBL students have higher mathematics communication skills than conventional pupils.Keywords: Problem Based Learning Model, Mathematical Communication Skills, Conventional Learning